Potential use of the SARS-CoV-2 monoclonal antibody sipavibart in people with multiple sclerosis: definition of different patient archetypes from an Italian expert group perspective - Zanetta, Chiara; Gasperini, Claudio; Amato, Maria Pia; Centonze, Diego; Gallo, Paolo; Patti, Francesco; Riva, Agostino; Filippi, Massimo (Journal of neurology, 2025)
Introduction Immunocompromised people, including people with MS (PwMS) remain at increased risk of severe COVID-19 outcomes, highlighting how this population needs additional preventive measures beyond current vaccination. Seven neurologists with experience in the MS field and one infectivologist discussed the use of COVID-19 pre-exposure prophylaxis (PrEP) in PwMS, identifying patients’ archetypes for PrEP with the monoclonal antibody sipavibart. Methods The following topics were discussed: description of the current SARS-CoV-2 infection scenario; identification of the characteristics of the fragile patient; identification of the ideal candidate for PrEP with sipavibart. The recommendations were then produced accordingly. Results Vaccination remains a crucial preventive measure for COVID-19. Age, male sex, and comorbidities are associated with severe outcomes among patients with MS. MS-specific risk factors include higher disability, a progressive disease course, a recent administration of steroids and the treatment with anti-CD20 agents, S1P receptor modulators, cladribine, and anti-CD52 antibodies. Pediatric patients and subjects with neuromyelitis optica spectrum disorder should also be considered fragile subjects. Subjects who could benefit from PrEP include: PwMS who present risk factors similar to the general population or who present disease-specific risk factors, non-vaccinated PwMS, and PwMS under S1P receptor modulators, anti-CD20 agents, alemtuzumab or cladribine and who present at least one risk factor similar to the general population or one disease-specific risk factor. Discussion Subjects with general or disease specific risk factors for severe infections, patients treated with S1P receptor modulators, anti-CD20 agents, alemtuzumab or cladribine, pediatric patients, and pregnant women with MS could represent the ideal candidates for PrEP with sipavibart.